A critical discourse analysis of the news coverage of the Palestinian-Israeli conflict in AJE and CNN news websites / Ashraf Z. R. Tantish - Tantish, Ashraf Z. R. (2012)
In the past fifteen years, language, ideology and power of the news articles of two prominent international news websites, namely Aljazeera English (AJE) and CNN has been a controversial topic. The current study explores intertextuality and its function in reproducing the underlying ideology and power relations in the news articles on Palestinian-Israeli conflict in the news Websites of AJE and CNN. The study adopted Fairclough’s (1995) approach to CDA, the Three Dimensional Framework, to examine the use and functions of intertextuality in 6 news articles of AJE and CNN. The study focuses on intertextuality, specifically in the inclusion and exclusion of the “voices” in the news articles through the use of direct and indirect reporting of speech. A Critical Discourse Analysis in the news articles of AJE and CNN reveals how the producers of news articles in the news websites construct and incorporate the various voices for ideological purposes. The study demonstrates that the way writers incorporated the voices in the news articles using the direct and indirect reported speech is found to be loaded with ideological bias. The study reveals that there is a relationship between the way writers report the voices of others in the news articles and the objectives of the writers which clearly show the relationship between language, ideology and power in the new articles of AJE and CNN. The study suggests that the issue of intertextuality in the news articles on to the Palestinian-Israeli conflict published in the international news Websites of AJE and CNN needs to be explored and examined in a broader political context which the news articles are embedded.